Development of new NIR-spectroscopy method combined with multivariate analysis for detection of adulteration in camel milk with goat milk. (15th April 2017) - Mabood, Fazal; Jabeen, Farah; Ahmed, Manzor; Hussain, Javid; Al Mashaykhi, Saaida A.A.; Al Rubaiey, Zainb M.A.; Farooq, Saim; Boqué, Ricard; Ali, Liaqat; Hussain, Zahid; Al-Harrasi, Ahmed; Khan, Abdul Latif; et al.
Highlights: Development of new NIR spectroscopy combined with multivariate methods to detect & quantify adulteration in camel milk with goat milk. To build PLS regression models. To build PCA and PLSDA models. Abstract: New NIR spectroscopy combined with multivariate analysis for detection and quantification of camel milk adulteration with goat milk was investigated. Camel milk samples were collected from Aldhahira and Sharqia regions of Sultanate of Oman and were measured using NIR spectroscopy in absorption mode in the wavelength range from 700 to 2500 nm, at 2 cm −1 resolution and using a 0.2 mm path length CaF2 sealed cell. The multivariate methods like PCA, PLS-DA and PLS regression were used for interpretation of NIR spectral data. PLS-DA was used to detect the discrimination between the pure and adulterated milk samples. For PLSDA model the R-square value obtained was 0.974 with 0.08 RMSE. Furthermore, PLS regression model was used to quantify the levels of adulteration from, 0%, 2%, 5%, 10%, 15% and 20%. The PLS model showed the RMSEC = 1.10% with R 2  = 94%. This method is simple, reproducible, having excellent sensitivity. The limit of detection was found 0.5%, while the limit of quantification was 2%.